Clinical Characteristics of Patients Responding to Once-Daily Basal Insulin Therapy in Korean Subjects with Type 2 Diabetes. Issue 4 (December 2015) - Song, Sun; Hwang, You-Cheol; Ahn, Kyu-Jeung; Cha, Bong; Song, Young; Lee, Dae; Lee, Byung-Wan
Abstract Introduction A1 chieve® (ClinicalTrials.gov identifier NCT00869908) was a 24-week observational study evaluating certain insulin analogs and not insulin analogs in general in 66, 726 people with type 2 diabetes (T2D) in routine clinical care in 28 non-Western countries. This study demonstrated that insulin analogs improved self-management and metabolic control in patients with T2D. We investigated the effectiveness and clinical characteristics of patients with T2D showing better response to basal insulin (BI) (detemir), using data from the A1 chieve study performed in Korea. Methods Subjects were classified into two groups according to the achievement of target glycated hemoglobin (A1c) level of <7.5%. Multivariate logistic regression analysis was performed to determine the variables independently associated with the achievement of target A1c level. Results Baseline A1c, postprandial glucose (PPG), difference between PPG and fasting plasma glucose, and duration of diabetes were independently associated with better response to BI after adjusting for other risk factors. Compared to patients with BI use at evening, those who took BI in the morning demonstrated a larger reduction in A1c level. Conclusion Once-daily BI therapy appears to be effective in Korean subjects with type 2 diabetes who had a shorter duration of diabetes and a smaller postprandial glucose excursion. Funding Novo Nordisk Pharma Korea and Novo Nordisk International Operations.